Barcos para la guerra. Soporte de la Monarquía Hispánica - Casado Soto, José Luis (Cuadernos de Historia Moderna, 2006)
During the early modern centuries, the Spanish nation played the lead in a process of European expansion that blurred all boundaries. The breaking of each and every oceanic horizon was only possible because the country had the appropriate ships and navigation systems, although the implicit knowledge in such communication and war resources still leaves a lot to be desired. This article attempts to draft a panoramic sketch of the state of this matter by considering some methodological aspects, and others which, in our view, characterize the various junctures which followed one another throughout the 16th, 17th and early 18th centuries. Ultimately, it seeks to motivate critical reflection and, in a rigorous way, enables to tackle the prevailing apparent contradiction between the pejorative state of international historiographic opinion, regarding the Spanish ships that constructed and maintained oceanic routes in the Modern Ages, and the axiom of the impossibility of a threefold political, economic and military preponderance, necessary to run an empire, if the technology and capacity of creation, renovation and adaptation available are not of superior quality than the rivals’.